1996
DOI: 10.1002/bjs.1800830317
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of inflammatory mediators related to organ failure in patients with acute pancreatitis

Abstract: Leucocyte activation and proinflammatory cytokine release (tumour necrosis factor (TNF) and interleukin 6 (IL-6)) are thought to contribute to the induction of a systemic inflammatory response, an acute-phase response and multiple organ failure in patients with acute pancreatitis. The serum concentration of TNF, soluble TNF receptors (sTNFR55 and sTNFR75), IL-6 and C-reative protein (CRP) in 58 patients with acute pancreatitis was assessed during the first 2 days of admission. Thirty patients had mild disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(125 citation statements)
references
References 27 publications
5
114
0
6
Order By: Relevance
“…Nos decidimos a determinar la IL-18, que algunos autores han considerado como marcador pronóstico de gravedad (14)(15)(16)(17)(18)(19)(20), así como el receptor-I soluble del TNF (sTNFRI) y el antagonista del receptor de la IL-1ß (IL1Ra) teniendo en cuenta, que en estudios previos (24), no se detectaron datos fiables en cuanto a los niveles séricos de sus correspondientes citocinas. En cuanto al sTNFRI, la significación estadística detectada a partir de las 48 horas que se mantiene a las 72 horas y a los 7 días, parece indicar que este pudiera tener valor pronóstico a partir del 2º día, lo cual se ha observado también en otros estudios donde se detecta elevación significativamente mayor del sTNFRI en relación con la gravedad, la existencia de necrosis pancreática y/o fallo multiorgánico (25)(26)(27)(28).…”
Section: Discussionunclassified
“…Nos decidimos a determinar la IL-18, que algunos autores han considerado como marcador pronóstico de gravedad (14)(15)(16)(17)(18)(19)(20), así como el receptor-I soluble del TNF (sTNFRI) y el antagonista del receptor de la IL-1ß (IL1Ra) teniendo en cuenta, que en estudios previos (24), no se detectaron datos fiables en cuanto a los niveles séricos de sus correspondientes citocinas. En cuanto al sTNFRI, la significación estadística detectada a partir de las 48 horas que se mantiene a las 72 horas y a los 7 días, parece indicar que este pudiera tener valor pronóstico a partir del 2º día, lo cual se ha observado también en otros estudios donde se detecta elevación significativamente mayor del sTNFRI en relación con la gravedad, la existencia de necrosis pancreática y/o fallo multiorgánico (25)(26)(27)(28).…”
Section: Discussionunclassified
“…The release of copious amounts of inflammatory mediators leads to microcirculatory disturbances and leukocyte-mediated release of arachidonic acid metabolites, oxygen-free radicals, nitrogen-oxygen compounds and proteases. These secondary inflammatory mediators may cause organ and cell injury and the whole process may ultimately develop into systemic multiple organ dysfunction syndrome (MODS) (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed that inflammatory mediators and microcirculation disorders (MCD) play very important roles in the pathogenesis of severe acute pancreatitis. It has been proposed that the systemic sequelae of AP arise from excessive leukocyte activation with the release of secondary inflammatory mediators, such as interleukin (IL)-1α, IL-6, IL-8, IL-10; tumor necrosis factor-α (TNF-α); platelet-activating factor (PAF); nitric oxide (NO); and phospholipase A 2 [6][7][8][9][10][11][12][13][14] . Excessive production of these mediators contributes to the induction of the systemic inflammatory response syndrome, acute phase response, and multiple organ failure [7,14] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the systemic sequelae of AP arise from excessive leukocyte activation with the release of secondary inflammatory mediators, such as interleukin (IL)-1α, IL-6, IL-8, IL-10; tumor necrosis factor-α (TNF-α); platelet-activating factor (PAF); nitric oxide (NO); and phospholipase A 2 [6][7][8][9][10][11][12][13][14] . Excessive production of these mediators contributes to the induction of the systemic inflammatory response syndrome, acute phase response, and multiple organ failure [7,14] . On the other hand, the pancreatic microcirculation is impaired in acute pancreatitis [15] .…”
Section: Introductionmentioning
confidence: 99%